The effect of consuming the hypercholesterolemia rationed food to the body weight of white rats wistar with administration of lactic acid bacteria - RIANI HARDININGSIH; NOVIK NURHIDAYAT (Society for Indonesian Biodiversity, 2006)
The consumption of food could influence the body weight of organisms. â€œHypercholesterolemia rationed foodâ€ is the food that increase the cholesterol on blood of rats. The purpose of this research was to study the effect of hypercholesterolemia rationed food to the body weight of white rats wistar with administration of Lactobacillus. In vivo research was done by using thirty rats that devided into three groups. Group I as Negative Control; Group II as Positive Control and Group III as The Treatment. The rat on Group I was given standart rationed food with physiological solution; Group II was given hypercholesterolemia rationed food and Group III was given Hypercholesterolemia rationed food with administration of Lactobacillus. The rationed food was given 20 g/rat/day. The weight of rats were balanced twice a week. The result of this research showed that the hypercholesterolemia rationed food could increase the body weight of rats; and administration of Lactobacillus could not decrease the body weight of rat with hypercholesterolemia rationed food. Â© 2006 Jurusan Biologi FMIPA UNS SurakartaKey words: hypercholesterolemia rationed food, the body weight, lactic acid bacteria, Lactobacillus